Upcycling post-consumer poly(lactic acid) (PLA) forcosmetic delivery systems: Synthesis and characterizationof PLA-based graft copolymers and microspheres - Brown, Zoë (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.